2008
DOI: 10.1111/j.1469-8749.2008.02054.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported health‐related quality of life in children and adolescents with myelomeningocele

Abstract: The aim of the study was to investigate self‐reported health‐related quality of life (HRQOL) in children and adolescents with myelomeningocele (MMC) and to examine the impact of clinical impairments and limitations in activities of daily living (ADL). Fifty patients (28 females, 22 males) between 8 and 16 years of age (mean age 12y 1mo [SD 2y 4mo]) with MMC from three German paediatric centres and their mothers completed standardized measures on HRQOL (KINDL‐R) and limitations in ADL (Childhood Health Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 23 publications
5
44
0
4
Order By: Relevance
“…In our population, the parents scored children in the low 80s and considerably below on the PODCI for all categories except upper extremity and physical function scores for both neurologic groups and in comfort scores for those children in the L2 and above group. This is in contrast to Leger [16] who reported that their sample of youth (age [15][16][17][18][19][20][21][22][23][24][25] with MM in the New England area had a high quality of life and participated in recreation and sports.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…In our population, the parents scored children in the low 80s and considerably below on the PODCI for all categories except upper extremity and physical function scores for both neurologic groups and in comfort scores for those children in the L2 and above group. This is in contrast to Leger [16] who reported that their sample of youth (age [15][16][17][18][19][20][21][22][23][24][25] with MM in the New England area had a high quality of life and participated in recreation and sports.…”
Section: Discussionmentioning
confidence: 75%
“…Parents of the 50 subjects were interviewed in person during the MM clinic using two HRQOL outcome tools: the PedsQL TM Version 4.0 [7,[24][25][26][27] parent version for young children (ages 5-7), children (ages [8][9][10][11][12], and the teen report (ages [13][14][15][16][17][18]; and the PODCI Version 2.0 [10] parent form for children (ages 2-18). Because of concerns about time and length of the instrument, 22% of the parents declined to complete the PODCI questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations